PENGARUH MEDIA LIDI PELANGI TERHADAP HASIL BELAJAR MATEMATIKA DI KELAS 1 SD NEGERI 1 WATUBELAH - Putri Andini; Hema Widiawati; Novan Hardiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine: 1) Is there a difference in the learning outcomes of grade 1 students of SD Negeri 1 Watubelah before and after using Lidi Pelangi media. 2) Does the use of Lidi Pelangi media have a significant effect on improving the mathematics learning outcomes of grade 1 students of SD Negeri 1 Watubelah. This study uses One Group Pretest-Posttest Design research. The instruments used are observation sheets and learning outcome tests. The subjects of the study were grade 1 students of SD Negeri 1 Watubelah. The results showed that the learning outcomes of students before using Lidi Pelangi media obtained an average pretest score of 54,4. While after using Lidi Pelangi media in grade 1 of SD Negeri 1 Watubelah, mathematics learning outcomes increased significantly, with an average posttest score of 86.8, and an increase in affective and psychomotor aspects reaching 88% and 92% respectively, proven by the T- test hypothesis test which obtained a t-test of 14,851 and a significant value of 0.000. Meanwhile, the hypothesis test of the Ngain test obtained 73,6381%. This means that the results of the n-gain test of students in mathematics learning have high criteria. So, it can be concluded that the use of Lidi Pelangi media on student learning outcomes in mathematics learning in class 1 of SD Negeri 1 Watubelah is very effective.